2020
DOI: 10.1088/1742-6596/1517/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation of university website: a case study

Abstract: Web-based public services become an important part in supporting the success of a university, but there are still many difficulties to use it. This study was conducted to evaluate whether Muhammadiyah Magelang University website has had the acceptability criteria of usability testing. The study was conducted using a questionnaire as a research instrument that consisted of 17 questions and filled by 95 respondents. Those questions grouped into five variables usability, there are learnability, efficiency, memora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The mobile money subscribers were satisfied with the features and functionalities of the G-MoMo applications, the information, and the display quality. This attribute was reported in other studies conducted by Byun et al (2020) The new mobile money subscribers found it easy to use the native G-MoMo applications because of the simplicity of the interfaces, features, and functionalities, which helped achieve total satisfaction (Byun et al, 2020;Merks et al, 2020;Lersilp et al, 2020;Sukmasetya et al, 2020;Al-Gayar et al, 2021;Kairy et al, 2021).…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...supporting
confidence: 53%
See 1 more Smart Citation
“…The mobile money subscribers were satisfied with the features and functionalities of the G-MoMo applications, the information, and the display quality. This attribute was reported in other studies conducted by Byun et al (2020) The new mobile money subscribers found it easy to use the native G-MoMo applications because of the simplicity of the interfaces, features, and functionalities, which helped achieve total satisfaction (Byun et al, 2020;Merks et al, 2020;Lersilp et al, 2020;Sukmasetya et al, 2020;Al-Gayar et al, 2021;Kairy et al, 2021).…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...supporting
confidence: 53%
“…Abidin et al (2019) recommended that applications must have help and documentation features explained in simple language and easily accessible. It was reported that the usability testing result showed that the native G-MoMo applications were highly efficient because mobile money subscribers could take less time to complete the given tasks accurately (Lynn et al, 2020;Byun et al, 2020;Hussain et al, 2020;Zakaria et al, 2020;Sukmasetya et al, 2020;Tyas & Khairunisa, 2020;Emanuela et al, 2020;Mubeen et al, 2020;A'bas et al, 2021;Putri et al, 2021).…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...mentioning
confidence: 99%
“…The users also agreed that they would remember navigating between G-MoMo applications pages the next time they use it. This is supported by (Alturki et al, 2020;Putri et al, 2021;Sukmasetya et al, 2020;Zakaria et al, 2020), who reported that the users easily remember the steps followed while using the applications. The participants reported having encountered fewer errors while using the G-MoMo applications.…”
Section: Discussionmentioning
confidence: 70%
“…Usability is a way that can be done to measure the usability level of the application [30]. The use of the Five Human Factors in the context of testing to investigate how content created in virtual reality can be delivered functionally [31]. In applications for educational purposes such as safety training, usability approaches such as the Five Human Factors are also useful to see the effectiveness of implementing a technology [29], [32] Five Human Factors consists of five main components [33].…”
Section: Literature Reviewmentioning
confidence: 99%